Improving the Understanding of Perianal Crohn Fistula Through 3D Modeling. Issue 6 (June 2018) - Sahnan, Kapil; Adegbola, Samuel O.; Tozer, Phillip J.; Gupta, Arun; Baldwin-Cleland, Rachel; Yassin, Nuha; Warusavitarne, Janindra; Faiz, Omar D.; Hart, Ailsa L.; Phillips, Robin K. S.; Lung, Phillip F. C.
Abstract : Supplemental Digital Content is available in the text